Modified silicas with different structure of grafted methylphenylsiloxane layer - Bolbukh, Yuliia (Nanoscale Res Lett, 2016)
The method of a chemical assembly of the surface polymeric layer with high contents of the modifying agent was developed. Powders of nanodispersed silica with chemisorbed polymethylphenylsiloxane (PMPS) were synthesized by solvent-free chemical assembly technique with a dimethyl carbonate (DMC) as scission agent. Samples were characterized using FTIR spectroscopy, transmission electron microscopy (TEM), atomic force microscopy (AFM), and elemental analysis (CHN analysis). Coating microstructure, morphology, and hydrophilic-hydrophobic properties of nanoparticles were estimated. The results indicate a significant effect of the PMPS/DMC ratio at each modification stage on hydrophobic properties of modified silicas. Modification with a similar composition of the PMPS/DMC mixture, even with different polymer amount at each stage, provides the worst hydrophobicity. Results suggest that the highest hydrophobicity (contact angle θ = 135°–140°) is achieved in the case when silica modified with the PMPS/DMC mixture using multistage approach that providing a formation of the monomolecular layer of polysiloxane at the first modification step. The characteristics of surface structure were interpreted in terms of density of polymer-silica bonds at the interfaces that, usually, are reduced for modified surfaces, in a coupling with conformation model that accented the shape of chains (arch- and console-like) adsorbed on solid surfaces.